PENGGAMBARAN SOSOK BAPAK DALAM NOVEL IL A JAMAIS TUÉ PERSONNE, MON PAPA KARYA JEAN-LOUIS FOURNIER - Endah Istiqomah Apriliani; Aquarini Priyatna Prabasmoro; Asep Yusup Hudayat (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
This study aims to examine the representation of father domination and the role of autobiographical fiction in resisting the father domination. This study attempts to address two issues: 1) The representation of name-of-the-father domination in a novel, and 2) the narrative resistance to the domination through autobiographical fiction in a novel. The novel used as research as research here is Jean-Louis Fournier’s Il A Jamais Tué Personne, Mon Papa. The analysis is using qualitative descriptive technique. The novel was analyzed using Lacanian psychoanalysis regarding the notion of name-of-the-father, Bourdieu’s theory of domination, and Austin’s autobiographical fiction concept. The study found that 1) there is the domination of name-of-the-father on Jean-Louis Fournier (the ‘I’ figure, narrator, and the author), and 2) the resistance towards the domination is showed through autobiographical fiction genre.